Data envelopment analysis on the non-finanacial company listed on FTSE bursa Malaysia KLCI stock market / Muhammad Ridwan Sumiri - Sumiri, Muhammad Ridwan (2021)
The FTSE Bursa Malaysia, also known as the FBM KLCI is a capitalisation-weighted stock market index composed by market capitalization of the 30 largest companies on the Bursa Malaysia. During 2006, Financial Times Stock Exchange (FTSE) has partnered with Bursa Malaysia to provide Malaysian market with a suite of indices to enhance Kuala Lumpur Composite Index (KLCI) by then KLCI was replaced by FTSE Bursa Malaysia KLCI. FTSE Bursa Malaysia KLCI is consist of two type of company which is non – financial companies and financial companies. Many institution traders or investor are looking for a company who have a good performance, in order for them to invest their money on that company, but the problem is to determine which one the right company or not can be very hard to determine. Measuring the performances of the listed stock companies in FBM KLCI can be very important to determine whether the company have running in fully capacity or not . Therefore, the aim of this study is to measure the overall performances based on efficiency score for non-financial companies listed on FBM KLCI Bursa Malaysia stock market. From the 30 companies listed on FBM KLCI there are only 22 non-financial companies in there have been choose for this research purpose with the time frames from 2016 until 2019. The researcher used Data Envelopment Analysis (DEA) method in measuring the efficiency score for the selected companies. The results of this report shows that there are only 8 companies which is Hartalega Holdings Berhad, Petronas Gas Berhad, Press Metal Berhad, Nestle Malaysia Berhad, PCHEM Berhad, Digi.Com, Maxis Berhad and Petronas Dagangan Berhad who are able to fully utilize all the input resources to maximize their output and have a good overall performances for 4 years consecutively. As conclusion, the company who have able to sustain their efficiency score for many years can be a good company to choose for an investor or traders to invest their money.